RESEARCH ON THE IMPACT OF GLOBAL INSTABILITY ON BUSINESS IN CONTEMPORARY TURBULENT CONDITIONS (Development Service Industry Management, 2023)
The given scientific article is dedicated to a thorough analysis of the impact of global instability on contemporary business in turbulent conditions. Conducting such research allows identifying key factors and challenges arising within the context of instability and discerning opportunities for business organizations.Particular attention is given to the development of strategies aimed at forming an antifragile approach in the face of global uncertainties. The research confirms that business organizations integrating antifragile principles become more adaptable and resilient in changing circumstances. This serves as a foundation for further developments in the field of strategic management, enhancing the resilience of business systems in the modern unpredictable world.The conclusions of the article propose specific practical approaches for the development of antifragile strategies for businesses. Understanding and implementing these strategies can be the key to stability and success for enterprises in unpredictable conditions. Moreover, the application of the antifragility concept can serve as a basis for further research and innovation in the field of business management.In summary, this scientific article opens new perspectives and provides practical recommendations that can serve as a guide for business leaders, researchers, and strategic planners to effectively confront the challenges of global instability and create resilient and dynamic organizations.
Keywords: antifragility; adaptability; strategy; global instability; business